Dekonstruksi Cerita Rakyat Indonesia dalam Iklan Televisi - Gunawan Wiradharma; Khusnul Fatonah; Dede Mahmudah (BPSDMP Kominfo Jakarta, 2020)
The challenge to maintain the sustainability of Indonesian folklore is big that it may cause the loss of pride in Indonesian folklore among the youth. One of the efforts made by PT Lasallefood Indonesia is by presenting a Marjan syrup advertisement themed Indonesian folklore in Ramadhan. This study describes how Indonesian folklore, a traditional cultural product, is deconstructed into a syrup product television advertising with its creative side in generating brand awareness to the audience. This is a qualitative research relying on Derrida's Deconstruction theory. The data in this study are the folklore of Timun Mas and Lutung Kasarung. The result is the deconstruction of the folklore in Marjan's advertisement is not entirely the same as the original story. The folklore presented has almost all been developed. Some have been reconstructed into advertisements with a new and modern storyline, even though the characters presented are still the same. Some characterizations have changed, but don't affect the essence of the story. The folklore story plot has all been almost developed. The brand is featured three times at every important and reasonable moment. This advertisement has made a breakthrough to introduce Indonesian folklore that is full of moral messages with a contemporary look. Tantangan untuk mempertahankan kelestarian cerita rakyat Indonesia semakin besar dengan banyaknya budaya global yang masuk ke Indonesia sehingga tidak menutup kemungkinan hilangnya rasa kebanggan terhadap cerita rakyat Indonesia di kalangan generasi muda. Salah satu upaya telah dilakukan oleh PT Lasallefood Indonesia dengan menghadirkan iklan sirop Marjan yang bertemakan cerita rakyat Indonesia menjelang dan hingga akhir Ramadhan. Penelitian ini bertujuan untuk mendeskripsikan bagaimana cerita rakyat Indonesia sebagai produk budaya tradisional didekonstruksi menjadi iklan televisi produk sirop serta melihat sisi kreativitasnya dalam memunculkan brand awareness kepada penonton. Metode yang digunakan dalam penelitian ini ialah metode kualitatif yang ditopang oleh teori dekonstruksi Derrida. Data dalam penelitian ini adalah cerita rakyat Timun Mas dan Lutung Kasarung. Hasil penelitian menjelaskan bahwa cerita rakyat yang ada dalam iklan Marjan mengalami dekonstruksi dan tidak sepenuhnya sama dengan cerita aslinya. Penokohan dan perwatakan ada yang mengalami perubahan, tetapi tidak memengaruhi esensi cerita. Alur cerita rakyat yang ditampilkan dalam iklan Marjan hampir semuanya telah dikembangkan. Brand sirop Marjan juga ditampilkan sebanyak tiga kali pada setiap momen penting dan masuk akal. Iklan ini telah melakukan terobosan untuk memperkenalkan cerita rakyat Indonesia yang sarat dengan pesan moral dengan tampilan kekinian.